High Levels of Variation Within Gene Sequences of Olea europaea L. - Cultrera, Nicolò G. M.; Sarri, Vania; Lucentini, Livia; Ceccarelli, Marilena; Alagna, Fiammetta; Mariotti, Roberto; Mousavi, Soraya; Ruiz, Consolacion Guerrero; Baldoni, Luciana (Frontiers in Plant Science, 2019)
Gene sequence variation in cultivated olive (Olea europaea L. subsp. europaea var. europaea), the most important oil tree crop of the Mediterranean basin, has been poorly evaluated up to now. A deep sequence analysis of fragments of four genes, OeACP1, OeACP2, OeLUS and OeSUT1, in 90 cultivars, revealed a wide range of polymorphisms along all recognized allele forms and unexpected allele frequencies and genotype combinations. High linkage values among most polymorphisms were recorded within each gene fragment. The great sequence variability corresponded to a low number of alleles and, surprisingly, to a small fraction of genotype combinations. The distribution, frequency and combination of the different alleles at each locus is possibly due to natural and human pressures, such as selection, ancestrality or fitness. Phylogenetic analyses of allele sequences showed distant and complex patterns of relationships among cultivated olives, intermixed with other related forms, highlighting an evolutionary connection between olive cultivars and the Olea europaea subspecies cuspidata and cerasiformis. This study demonstrates how a detailed and complete sequence analysis of a few gene portions and a thorough genotyping on a representative set of cultivars can clarify important issues related to sequence polymorphisms, reconstructing the phylogeny of alleles, as well as the genotype combinations. The identification of regions representing blocks of recombination could reveal polymorphisms that represent putatively functional markers. Indeed, specific mutations found on the analyzed OeACP1 and OeACP2 fragments seem to be correlated to the fruit weight.